2005
DOI: 10.1039/b505484b
|View full text |Cite
|
Sign up to set email alerts
|

A new series of luminescent phosphine stabilised platinum ethynyl complexes

Abstract: A series of cis-platinum ethynyl complexes with the general formula cis-[Pt(dppe)(C[triple bond]CR)2](dppe = 1,2-bis(diphenylphosphino)ethane; R = C6H4-p-NO2 1, C6H4-p-CH3 2, C6H4-p-C[triple bond]CH 3 and C6H4-p-C6H4-p-C[triple bond]CH 4) have been prepared by the coupling reaction of cis-[Pt(dppe)Cl2] with two equivalents of the appropriate alkyne. The new complexes have been fully characterized by spectroscopic techniques, and the cis square planar arrangement at the platinum centre has been confirmed by sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 66 publications
(15 reference statements)
3
30
0
Order By: Relevance
“…These bands have been assigned to the π-π * transition of the acetylenic fragment with LMCT character due to the mixing between π * (C≡C-R) and platinum (n + 1)p orbital. Similar spectroscopic features are reported in the related metal acetylide systems (Wong et al 2004, Saha et al 2005, Sina et al 2015. Antibacterial activity: The antibacterial activities of sugar-containing iodo compound 1, ethynyl compounds 2 and 3, and platinum complexes 4 and 5 were tested against bacteria Escherichia coli, Proteus penneri, Klebsiella oxytoca and Pseudomonas aeruginosa.…”
Section: Synthesis and Characterizationmentioning
confidence: 74%
See 3 more Smart Citations
“…These bands have been assigned to the π-π * transition of the acetylenic fragment with LMCT character due to the mixing between π * (C≡C-R) and platinum (n + 1)p orbital. Similar spectroscopic features are reported in the related metal acetylide systems (Wong et al 2004, Saha et al 2005, Sina et al 2015. Antibacterial activity: The antibacterial activities of sugar-containing iodo compound 1, ethynyl compounds 2 and 3, and platinum complexes 4 and 5 were tested against bacteria Escherichia coli, Proteus penneri, Klebsiella oxytoca and Pseudomonas aeruginosa.…”
Section: Synthesis and Characterizationmentioning
confidence: 74%
“…UV-Vis spectroscopy is used to understand the π-interaction between the metal and ethynyl group in the metal ethynyl complexes (Saha et al 2005, Younus et al 1998, Fujikura et al 1975. A broad band at 250-360 nm was observed in the spectrum of mono-and bis-ethynyl complex 4 and 5.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent works, the authors reported the synthesis of platinum-poly-ynes with phosphines other than tri-n-butylphosphine. These include platinum ethynyl conplexes with 1,2-bis(diphenylphosphinoethane), dppe, - (Saha et al 2005) and tri-tolylphosphines containing platinum poly-yne polymers i.e.…”
Section: Introductionmentioning
confidence: 99%